Starswarm : a Jupiter novel - Pournelle, Jerry (New York : Tom Doherty Associates, 1999)
Kip has never known any life but his existence at the protected laboratory compound known as Starswarm Station. And for all that time he has heard the Voice: an artificial intelligence chip implanted in his skull. It guides him and helps protect him from the planet's many dangers, including roaming bands of hostile centaurs and "haters." But the startling discovery of who put the chip in his head - and why - leads Kip to revelations that could threaten the safety of the entire compound.
Keywords: Extraterrestrial bases -- Fiction; Fantasy fiction